The right of relatives of persons who disappeared during the Spanish Civil War to appeal and obtain redress - Capellà i Roig, Margalida (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
This study focuses on the right to economic reparation and the right to know the fate or whereabouts of civilians who disappeared during the Civil War in Spain and to recover their remains. The objective is to explain what remedies exist in Spanish law so that relatives of the civilian victims of the disappearances related to the Civil War and Franco’s repression can demand a judicial investigation into the events that occurred, the location and exhumation of the disappeared and, furthermore, a reparation for the damage suffered, specifically for the inhuman and cruel treatment inflicted by action or omission on these relatives both during the mentioned periods and even in the current democracy. I ask if these remedies are effective in accordance with international standards and if the planned remedy is adequate, effective and quick.